Effects of the Off-Label Drug Prescription in the Paediatric Population in Spain from the Adoption of the Latest European Regulation: A Pre-Post Study - Irene Lizano-Díez; Itziar Aldalur-Uranga; Carlos Figueiredo-Escribá; Cecilia F. Lastra; Eduardo L. Mariño; Pilar Modamio (MDPI AG, 2021)
The year 2021 marks the 15th anniversary of the Paediatric Regulation (1901/2006/EC) in Europe. The main aim of the study was to conduct a pre-post comparison on the annual off-label prescription rates in the under-18 population in Spain and assess the potential influence of the Paediatric Regulation adoption. An observational study in the paediatric population was performed. Four cross-sectional annual periods, one before and the three latest periods after the adoption of the Regulation, were compared. Prescriptions in the primary health care setting were sorted by age group and drug and off-label status were determined. The number of off-label prescriptions issued by paediatricians was over two million per year. Prior to the adoption of the Paediatric Regulation, the off-label prescription rate was estimated at 7% of total prescriptions. Although the increase in the off-label rate over the study periods was mild, it was statistically significant (OR: 1.045; 95% CI: 1.043-1.046; p < 0.05). One of the most vulnerable population groups was neonates and infants up to 1 year, in which the off-label prescription rates showed the highest increase during the post follow-up period, which was statistically significant (OR: 4.270; 95% CI: 4.253-4.287; p < 0.05). The findings can help raise awareness and advocate for the development and authorization of medicines for children in the primary health care setting.